Harnessing enhanced rock weathering for carbon neutrality: potential and challenges in China - Cong, Lianghan; Lu, Shuaiyi; Jiang, Pan; Zheng, Tianqi; Zhang, Yanjun; Lü, Xiaoshu; Yu, Ziwang; Xu, Tianfu (Elsevier, 2025)
The escalating urgency of global climate change underscores the need for effective strategies to manage atmospheric CO₂ concentrations. Enhanced rock weathering (ERW) has emerged as a promising carbon removal technology. By applying powdered silicate rocks rich in calcium and magnesium, such as basalt, the dissolution process can be accelerated to sequester CO₂ in the form of dissolved inorganic carbon (DIC) within soil porewater, which is ultimately transported to the ocean, achieving long-term carbon storage. Using a life cycle assessment (LCA) framework, this study evaluates the feasibility of basalt-based ERW in China, focusing on its environmental and economic implications across various application scenarios. The findings highlight that basalt particle size and environmental conditions are critical determinants of weathering efficiency. Smaller particles, elevated temperatures, and acidic soils enhance dissolution rates but also result in higher energy consumption for grinding and increased carbon emissions. China's extensive basalt reserves, diverse climatic conditions, and vast agricultural lands create favorable conditions for large-scale ERW implementation. Nationwide application of basalt at p80 = 100 μm could sequester 0.2 Gt CO₂ by 2100, while finer particles (p80 = 10 μm) could achieve 0.5 Gt by 2060. Despite its potential, ERW faces challenges, including heavy metal release, uncertainties in long-term weathering rates, and cost constraints.
Keywords: Carbon dioxide storage; Life cycle assessment; Enhanced rock weathering; Basalt mineralization; China climate target; Energy Technology; Energiatekniikka; Energy Technology; Energiatekniikka